Sol-Gel Deposited Porogen Based Porous Low-k Thin Films for Interlayer Dielectric Application in ULSI Circuits - Yogesh S. Mhaisagar; A.M. Mahajan (Журнал нано- та електронної фізики)
Porous SiO2 low-k thin films with low dielectric constant were successfully deposited by sol-gel spin-coating technique. The films were deposited by using Tertaethylorthosilicate (TEOS) as a precursor solution and HF was used as an acid catalyst solution. The Tween80 with different volumetric concentrations i.e. 0.0 ml, 0.5 ml and 0.7 ml was used as a pore generator to lower the dielectric constant of the films by introducing the porosity in the films matrix. The thickness and refractive index (RI) of low-k thin films have been measured by Ellipsometer. The refractive index and thickness of the films observed to be decreasing with increase in Tween80 concentration. The chemical bonding structures of films were analyzed by using Fourier transform infrared spectroscopy (FT-IR) spectroscopy and the stretching, bending and rocking peaks appear at 1077 cm – 1, 967  cm – 1, 447  cm – 1 respectively confirm the formation of Si-O-Si network. The RIs of the films deposited at 0 ml, 0.5 ml and at 0.7 ml of Tween80 concentration are found to be 1.34, 1.26, and 1.20 respectively. Based on RI values of the films, the porosity percentage, density and dielectric constant have been calculated by standard formulation method. The increase in porosity percentage of films from 3 % to 55 % with increase in Tween80 concentration reveals that, the most of the hydroxyl group and porogen get evaporated and form more voids in the films. This increase in porosity percentage causes to lower the dielectric constant of films and was found to be 2.26 at the 0.7 ml of Tween80 concentration. Such porogen based low dialectic constant thin films can be suitable for interlayer dielectric (ILD) applications in ULSI circuits.